Using malmquist TFP index for evaluating agricultural productivity: Agriculture of Türkiye NUTS2 regions - TEKİNER MOĞULKOÇ, HATİCE (My University, 2022)
Agriculture is one of the main economic sectors in Türkiye. Therefore, a performance evaluation is essential for an improvement in agricultural sector. In this study, the productivity of Turkish agricultural sector was analyzed for the years between 2006-2015. A non-parametric technique, Data Envelopment Analysis (DEA) based Malmquist index method, was applied to calculate the Total Factor Productivity (TFP) indices for agriculture in 26 NUTS2 (The Nomenclature of Territorial Units for Statistics) regions of Türkiye for the selected 10-year period. Total agricultural production value is used as the output variable and six input variables are selected as: land, labor, machine, livestock and government investment. The analysis was conducted via the computer program DEAP2.1. The result reveals that agricultural TFP of regions has decreased by 2% annually on average. The maximum TFP growth in agriculture occurred between 2007 and 2008 with a mean increase of 12% in overall TFP of regions. On the other hand, the greatest regression in the overall TFP was observed in 2010-2011 period by a decrease of 13%.
Keywords: Malmquist Index; Total factor Productivity; Regions of Türkiy; Agriculture